INVESTASI PERUSAHAAN MULTINASIONAL DALAM BIDANG EKONOMI KREATIF INDUSTRI VIRTUAL YOUTUBING DI INDONESIA TAHUN 2020-2023 (STUDI KASUS: HOLOLIVE PRODUCTION) - Respati Pakusadewo (2024)
This research aims to find out the impact of foreign corporation investment in the field of Virtual YouTubing in Indonesia and to look at Virtual YouTubing sector development on the global creative economy and its development in Indonesia. This research uses the concepts of Cultural Globalization, Foreign Direct Investment, Multinational Corporations, Creative Economy, and Virtual YouTubers. The method used is qualitative method to explain the Virtual YouTubers business sector with a case study of the company Hololive Production. The data collection techniques used were literature study, documentation study, and conducting interviews. The data analysis technique used is Miles and Huberman's method, namely summarizing data, displaying data, and drawing and verifying conclusions. The research results show that Hololive Production is superior in several ways compared to local companies in Indonesia, the most important of which are resources such as technology and facilities, and also the mindset of the people of Indonesia and Japan which have very different receptions towards the Virtual YouTube industry. This research found that from the period 2020 to 2023, the VTubing industry in Indonesia only experienced growth but did not experience deeper and more comprehensive development. However, it cannot be denied that this industry still has enormous potential and can benefit Indonesia's creative economy industry.